Melatonin promotes uterine and placental health: Potential molecular mechanisms - Chuffa, Luiz Gustavo de Almeida [UNESP]; Lupi, Luiz Antonio [UNESP]; Cucielo, Maira Smaniotto [UNESP]; Silveira, Henrique Spaulonci [UNESP]; Reiter, Russel J.; Seiva, Fábio Rodrigues Ferreira (MDPI, 2020)
The development of the endometrium is a cyclic event tightly regulated by hormones and growth factors to coordinate the menstrual cycle while promoting a suitable microenvironment for embryo implantation during the “receptivity window”. Many women experience uterine failures that hamper the success of conception, such as endometrium thickness, endometriosis, luteal phase defects, endometrial polyps, adenomyosis, viral infection, and even endometrial cancer; most of these disturbances involve changes in endocrine components or cell damage. The emerging evidence has proven that circadian rhythm deregulation followed by low circulating melatonin is associated with low implantation rates and difficulties to maintain pregnancy. Given that melatonin is a circadian-regulating hormone also involved in the maintenance of uterine homeostasis through regulation of numerous pathways associated with uterine receptivity and gestation, the success of female reproduction may be dependent on the levels and activity of uterine and placental melatonin. Based on the fact that irregular production of maternal and placental melatonin is related to recurrent spontaneous abortion and maternal/fetal disturbances, melatonin replacement may offer an excellent opportunity to restore normal physiological function of the affected tissues. By alleviating oxidative damage in the placenta, melatonin favors nutrient transfer and improves vascular dynamics at the uterine–placental interface. This review focuses on the main in vivo and in vitro functions of melatonin on uterine physiological processes, such as decidualization and implantation, and also on the feto-maternal tissues, and reviews how exogenous melatonin functions from a mechanistic standpoint to preserve the organ health. New insights on the potential signaling pathways whereby melatonin resists preeclampsia and endometriosis are further emphasized in this review.
Keywords: Circadian clock; Decidualization; Endometriosis; Implantation; Melatonin; Placenta; Uterine receptivity